Permeability of abortion care in the Netherlands: a qualitative analysis of women's experiences, health professional perspectives, and the internet resource of Women on Web. Issue 1 (1st January 2021) - Holten, Lianne; de Goeij, Eva; Kleiverda, Gunilla
Abstract: Despite a relatively permissive abortion law, women in the Netherlands encounter difficulties in accessing abortion care. Little is known about their experiences. This study explores women's experiences with (online) abortion services and relevant health professionals' experiences delivering care, with the goal of identifying key barriers encountered by abortion-seekers in the Netherlands. An exploratory qualitative research design with a constructivist approach and an abbreviated grounded theory method was used. Interviews with 20 women who had had an abortion and 14 health professionals who provide abortion care, and 200 emails of women seeking abortion care through the non-governmental organisation Women on Web, were coded inductively and deductively (using the Candidacy Framework) thereby generating themes. Abortion-seekers faced barriers including: (i) burden of taboo, (ii) vulnerability (emotional, financial, and social), (iii) health professional evaluation and (iv) disempowerment and distress. The overarching theme was women's lack of autonomy in access to abortion care. The key barriers to abortion access in the Netherlands are the institutionalisation of taboo in abortion law and care, complex candidacy regulations, lack of permeability for certain marginalised groups, and women's inability to speak openly about abortion. To increase the permeability of abortion care, and thereby women's autonomy, legislators and policy-makers must trust women to make their own reproductive decisions and avoid actions that stigmatise abortion and hinder access to care, while actively developing systemic support for vulnerable groups.